PENGARUH MODEL RADEC (READ-ANSWER-DISCUSS-EXPLAIN-CRATE) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS IV SEKOLAH DASAR - Khofifa Yuliar Fiyani; Achmad Fanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the RADEC learning model on the reading comprehension skills of fourth grade elementary school students. This study uses a quantitative method with a Posttest-Only Control Group Design . The population in this study were all fourth grade students at SDN Dr. Soetomo V Surabaya in the 2024/2025 academic year. The sample used in this study was all students of class IVA as the experimental class and class IVB as the control class at SDN Dr. Soetomo V Surabaya in the 2024/2025 academic year. The data collection technique for this study was filling out the post-test sheet directly which was carried out in the SDN Dr. Soetomo V Surabaya environment. Data analysis was carried out by validity testing, prerequisite testing, and hypothesis testing. The hypothesis test analysis technique used an independent t-test sample which showed a Sig - 2 tailed result of 0.000 <0.05 so that it can be stated that there is an effect of the RADEC learning model on the reading skills of fourth grade elementary school students at SDN Dr. Soetomo V Surabaya.